The Role of School Administration Personnel in Improving the Quality of Service at SD Negeri 004 Palembang - Nurlia, Ita; Widayatsi, Tri; Mulyadi, Mulyadi (Universitas Pahlawan Tuanku Tambusai, 2026)
School administration personnel are an integral part of the education management system whose role is to ensure that school governance runs in an orderly, effective, and sustainable manner. However, in practice, the existence of administrative personnel often receives less attention than educators and tends to be seen as limited to carrying out technical tasks. This study aims to analyze the role of administrative personnel in improving the quality of educational services at SD Negeri 004 Palembang by focusing on aspects of the implementation of duties, responsibilities, competencies, and obstacles faced. The research uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews with administrative staff, principals, and teachers, as well as documentation studies of school administrative archives. The results of the study show that although the number of administrative personnel is not ideal and the workload is relatively high, their contribution is very significant in data management, information services to school residents and parents, infrastructure management, and the preparation of institutional reports. The ability to master information technology and good internal coordination also improves service quality. Improving service quality can be done through the arrangement of task divisions, competency training, and strengthening the digital-based management system on an ongoing basis.